Urban climate adaptation and mitigation - Sharifi, Ayyoob; Khavarian, Amir (Elsevier, 2022)
Uniquely focused on the contributions smart cities can make to climate change resilience, Urban Climate Adaptation and Mitigation offers evidence-based scientific solutions for improving cities' abilities to prepare for, recover from, and adapt to global climate-related events. Beginning with the observation of global environmental change, this book explores what sustainable smart projects are, how they are adopted and evaluated, and how they can address climate change challenges. It brings together a wide variety of disciplines such as planning, transportation, and waste management to address issues related to climate change adaptation and mitigation in cities.In general, many social science researchers lack cohesive, broad-based literature knowledge; Urban Climate Adaptation and Mitigation bridges this gap and informs different types of stakeholders on how they can enhance their preparation abilities to enable real-time responses and actions. Therefore, it is a valuable reference for researchers, professors, graduate students, city planners, and policy makers. Application-focused throughout, this book explores the complexities of urban systems and subsystems to support researchers, planners, and decision makers in their efforts toward developing more climate-resilient smart cities.